2008
DOI: 10.1111/j.1746-1561.2008.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Students With Chronic Diseases: Nature of School Physician Support

Abstract: A portion of students with special health care needs benefited from district referral to a school physician consultant. Whether some of these referrals can be avoided if school personnel and students' own physicians are supported and trained to communicate more effectively with one another needs to be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…16 Collaboration between community clinicians and school physicians, such as the use of telemedicine technology for communication by physicians in partnerships with schools, 17 is an effective approach to ensuring that families receive consistent messages from all asthma care clinicians. [18][19][20][21] Although many studies have documented excessive school absenteeism caused by asthma, 22 , 23 recent studies have shown that the percentage of attendance among students with asthma can equal that of students without asthma when the former receive evidence-based care that includes school-based asthma services. 24 , 25 Examples of evidence-based school asthma services include having a full-time nurse, or having a school-based health clinic.…”
Section: Identify Students With Asthmamentioning
confidence: 98%
“…16 Collaboration between community clinicians and school physicians, such as the use of telemedicine technology for communication by physicians in partnerships with schools, 17 is an effective approach to ensuring that families receive consistent messages from all asthma care clinicians. [18][19][20][21] Although many studies have documented excessive school absenteeism caused by asthma, 22 , 23 recent studies have shown that the percentage of attendance among students with asthma can equal that of students without asthma when the former receive evidence-based care that includes school-based asthma services. 24 , 25 Examples of evidence-based school asthma services include having a full-time nurse, or having a school-based health clinic.…”
Section: Identify Students With Asthmamentioning
confidence: 98%
“…Overall, a school physician can become a positive liaison between the medical home, the family, and the school. 8 Table 1 contains a nonexclusive list of essential areas of expertise required of a school physician. one-on-one nurses and door-to-door transportation Reviews of emergency care plans for children with life-threatening conditions.…”
Section: Critical Knowledge Base For Physicians Working In the Schoolmentioning
confidence: 99%